Phosphorus Recycling from an Unexplored Source by Polyphosphate Accumulating Microalgae and Cyanobacteria—A Step to Phosphorus Security in Agriculture - Mukherjee, Chandan; Chowdhury, Rajojit; Ray, Krishna (Frontiers in Microbiology, 2015)
Phosphorus (P), an essential element required for crop growth has no substitute. The global food security depends on phosphorus availability in soil for crop production. World phosphorus reserves are fast depleting and with an annual increase of 2.3% in phosphorus demand, the current reserves will be exhausted in coming 50-100 years. India and other Western countries are forced to import phosphorus fertilizers at high costs to meet their agricultural demands due to uneven distribution of phosphate rocks on earth. The present study from India, aims to draw attention to an unnoticed source of phosphorus being wasted as parboiled rice mill effluent and subsequent bio-recovery of the valuable element from this unconventional source. The research was conducted in West Bengal, India, a state with the highest number of parboiled rice mills where its effluent carries on an average 40 mg/L of soluble phosphorus. Technology to recover and recycle this wastewater P in India in a simple, inexpensive mode is yet to be optimized. Our strategy to use microalgae, Chlorella sp. and cyanobacteria, Cyanobacterium sp., Lyngbya sp. and Anabaena sp. to sequester the excess phosphorus from the effluent as polyphosphate inclusions and its subsequent recycling as slow and moderate release phosphorus biofertilizers to aid plant growth, preventing phosphorus loss and pollution, is a contemporary venture to meet the need of the hour. These polyphosphate accumulating microorganisms play a dual role of remediation and recovery of phosphorus, preliminarily validated in laboratory scale.